MODEL PERENCANAAN SEKOLAH MENENGAH KEJURUAN PENYELENGGARA KELAS STANDAR INDUSTRI - Suroto Suroto (Jurnal Taman Vokasi, 2017)
The purpose of this research is to formulate the model of the planning of the Organizer School of industry standard class. This type of research uses a qualitative approach with the location in SMK PIRI 1 Yogyakarta on the package of Light Vehicle Engineering expertise. Data collection techniques used interviews, observations, and documentary observations. Testing of data validity is done by triangulation of data, auditing, and review of an informant. The technique of analysis through data reduction phase, data presentation, conclusion. The results of the research indicate that the School Planning of industry standard class organizers involves partner industry in synchronizing the industry curriculum with the curriculum of the government into implementation curriculum, student selection, preparation of facilities and infrastructure, teacher competence and teaching materials. Industrial standard class planning is done through the selection phase of students in the third semester, the second phase of the industry-standard teaching and learning process in the third semester until semester VI, the third stage through competency test in the 6th semester.